UTILIZING PHILOLOGY TO FACILITATE INTERCULTURAL COMPREHENSION (American Journal of Research in Humanities and Social Sciences, 2024)
This paper delves into the utilization of philology as a mechanism to cultivate intercultural comprehension. Employing an interdisciplinary perspective, it scrutinizes how philological methodologies aid in deciphering and appreciating the cultural subtleties interwoven within language. By synthesizing theoretical constructs and empirical investigations, this study sheds light on philology's role in bridging the linguistic and cultural chasms, thereby enriching cross-cultural communication and understanding.